Study on discrete prediction model for mechanical behavior of buried pipelines under the influence of differential frost heave - Xiyan Zhang; Lei Chen; Lipei Guan (Scientific Reports)
Abstract Pipelines are the primary mode of oil and gas transport in cold regions. Differential frost heaving of frozen and non-frozen soil masses can damage such pipelines, posing economic and environmental risks. The present study investigates the mechanical behaviors of buried pipelines under differential frost heaving forces. A discrete forecasting model of these mechanical behaviors based on frost heaving springs is proposed. The relationship between the frost heaving amount and force at any moment is established using the Takashi empirical equation and the corresponding development of frost depth. On this basis, the properties of nonlinear frost heaving springs are disclosed. A model of pipeline mechanical state is derived to understand the deformation and stress at any moment, allowing the dynamic prediction of mechanical behaviors. The model is applied to two case studies involving the Caen and Alaska buried pipelines. The modeling results agree well with measurements taken at these pipelines, and the discrete descriptions of their mechanical modes are effective. A sensitivity analysis of the modeling results for pipelines of different size was conducted, providing a theoretical foundation for the optimal design of buried pipelines in cold regions.